Does cardiac resynchronization therapy restore peripheral circulatory homeostasis?. (13th October 2017) - Ajaero, Chukwudiebube N.; Chong, Cher‐Rin; Procter, Nathan E.K.; Liu, Saifei; Chirkov, Yuliy Y.; Heresztyn, Tamila; Chan, Wai Ping Alicia; Arstall, Margaret A.; McGavigan, Andrew D.; Frenneaux, Michael P.; Horowitz, John D.
Abstract: Aims: To evaluate whether peripheral circulatory 'remodelling' as measured by changes in vascular compliance and in markers of nitric oxide signalling contributes to patient response to cardiac resynchronization therapy (CRT). Methods and results: Effects of CRT were evaluated in 33 patients pre‐procedure and 6 months post‐procedure. Peak oxygen consumption, 6 min walk distance, New York Heart Association class, and quality of life score were evaluated. Augmentation index and its interactions with nitric oxide (NO) were evaluated by applanation tonometry. Platelet NO responsiveness and content of thioredoxin‐interacting protein were assessed. Plasma concentrations of N‐terminal proBNP, asymmetric and symmetric dimethylarginine (SDMA), high sensitivity C‐reactive protein, catecholamines, and matrix metalloproteinases‐2 and ‐9 were assessed. Despite significant improvement in 6 min walk distance ( P  = 0.005), New York Heart Association class ( P  < 0.001), quality of life ( P  = 0.001), and all echocardiographic parameters post‐CRT, there were no significant changes in augmentation index measurements, thioredoxin‐interacting protein content, and platelet NO response. Significant falls in N‐terminal proBNP ( P  = 0.008) and SDMA ( P  = 0.013; independent of renal function) occurred. Falls in SDMA predicted reduction in high‐sensitivity C‐reactive protein ( P  = 0.04) and increases in peak oxygen consumption ( P  = 0.04). There were no correlations between changes in echocardiographic parameters and those in vascular function. Conclusions: These data suggest that the beneficial effects of CRT over 6 months are independent of any change in peripheral NO‐related signalling. However, there is evidence that suppression of inflammation occurs, and its magnitude predicts extent of clinical improvement.